(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Two systems of linear singularly perturbed problems in first order partial derivatives were considered. This system depends on a small parameter, and the small parameter exists in the left and right hands of it. Also, we prove the uniqueness of this solution is uniform in the space and asymptotic approximation of any rank was constructed.